2023
DOI: 10.1007/s10336-023-02065-9
|View full text |Cite
|
Sign up to set email alerts
|

Breeding biology of the African Pygmy Falcon: long-term variation and seasonal decline in breeding performance of an arid zone raptor

Abstract: Birds of prey are apex predators and understanding their life history can serve as a valuable baseline for investigating their ecological role. Pygmy Falcons (Polihieraxsemitorquatus), Africa’s smallest diurnal raptor, have evolved to be obligate associates of Sociable Weaver (Philetairussocius) colonies throughout their southern African range. As a predator, Pygmy Falcons likely impact prey communities in this system including their host and other colony associates. However, no study has explored their breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Our results suggest that snakes forage in colonies more often when weavers are breeding and when colonies are larger, although part of this signal might be explained by snakes spending longer in larger colonies. Interestingly, falcons also favour occupying bigger weaver colonies (Olubodun et al 2023). Nevertheless, despite falcons being able to repel snakes from weaver colonies, we found that this did not lead to an increase in reproductive output for weavers.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Our results suggest that snakes forage in colonies more often when weavers are breeding and when colonies are larger, although part of this signal might be explained by snakes spending longer in larger colonies. Interestingly, falcons also favour occupying bigger weaver colonies (Olubodun et al 2023). Nevertheless, despite falcons being able to repel snakes from weaver colonies, we found that this did not lead to an increase in reproductive output for weavers.…”
Section: Discussionmentioning
confidence: 52%
“…Biotic and abiotic conditions may also affect the outcomes of nesting associate interactions (G€ otmark 1989, Larsen & Grundetjern 1997, Quinn & Ueta 2008, Canestrari et al 2014. For example, the variable timing of breeding of the two species (Mares et al 2017, Olubodun et al 2023) holds significant consequences for the net fitness outcomes. Predation pressure will also alter the net outcomes; weaver nest predation pressure by snakes (and indeed falcons) may change due to environmental conditions, especially in arid environments where resource availability fluctuates between abundant and scarce (Hillel & Tadmor 1962, Rosenzweig 1968.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations